The wondering Juan the Philippine culture and nationalism in I Juander - Villaluz, Tricia Marie Blanco; Santos, Josefina C.; University of the Philippines. College of Mass Communication (Quezon City University of the Philippines Diliman, 2013)
"This study explored how the representation of Philippine culture in the TV program I Juander evokes the sense of Filipino nationalism as defined by Jose Abueva. I situated the current state of Philippine broadcasting system which is dominated by Western ideas brought about by colonization and globalization. This realization made me utilize narrative analysis to scrutinize 7 episode of I Juander from November 24, 2012 to December 26, 2012 and I discovered that I Juander's usage of historical analysis, social experiments, and case studies in its narrative helped portray that Filipinos have shared history, culture, and experiences with regards to different Philippine culture. Furthermore through its portrayal of symbols on Filipino nationhood, I Juander is able to accord to Abueva's definition of nationalism as love of country and nation. This depiction of national symbols is then called by Abueva as Filipinism. The program however lacked in representing the other three definitions. I Juander as a mass communication message evokes Filipinism through its portrayal of national symbols and emphasizing the shared history, culture and experiences of Filipinos. However, for a fuller realization of Filipino nationalism, the program must portray issues that our country is facing today so it can stimulate the minds of its viewers and the Filipino people to act on the development of the Philippines."
Vita.
Undergraduate thesis
Keywords: Mass media and culture -- Philippines; National characteristics, Philippine; Television programs -- Philippines